2000
DOI: 10.1046/j.1365-2648.2000.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Family members’ experience of familial amyloidotic polyneuropathy disease — an infernal struggle and a fact of life

Abstract: Familial amyloidotic polyneuropathy is a fatal, hereditary, systemic, progressive amyloidosis. No previous qualitative study of the family members' experience of the disease has been published. The purpose of this phenomenological study was to understand the lived experience of family members whose nearest and dearest suffered from familial amyloidotic polyneuropathy. In-depth interviews were conducted with six family members. The analysis of the data was inspired by Colaizzi's method. Two major theme categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Two major themes emerged: the difficulty and the need to accept a disease with such serious implications for the lives in the whole family. 20 A study of Portuguese TTR-FAP Val30Met patients on transgenerational aspects of the illness to understand the role of older generations has shown that there was an intergenerational flow of support, and that communication was higher among affected members and between mothers and affected daughters. 21 The aims of this study were to (1) evaluate how TTR-FAP Val30-Met affected patients and pre-symptomatic carriers perceive their family´s functioning, (2) compare the perception of the family system by these two groups to that of their partners, and (3) compare the above mentioned perceptions to those of patients with multiple sclerosis (MS).…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Two major themes emerged: the difficulty and the need to accept a disease with such serious implications for the lives in the whole family. 20 A study of Portuguese TTR-FAP Val30Met patients on transgenerational aspects of the illness to understand the role of older generations has shown that there was an intergenerational flow of support, and that communication was higher among affected members and between mothers and affected daughters. 21 The aims of this study were to (1) evaluate how TTR-FAP Val30-Met affected patients and pre-symptomatic carriers perceive their family´s functioning, (2) compare the perception of the family system by these two groups to that of their partners, and (3) compare the above mentioned perceptions to those of patients with multiple sclerosis (MS).…”
Section: Livermentioning
confidence: 99%
“…In order to understand the experiences lived by family members, a phenomenological study was conducted in Sweden, where members of six families were interviewed. Two major themes emerged: the difficulty and the need to accept a disease with such serious implications for the lives in the whole family …”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult for families to accept that the person they love is seriously ill and that they themselves are unable to help. Nevertheless, mothers perceive their presence as critical for keeping their children healthy and strong, and families want to be able to spend time with their ill members when they are hospitalized or institutionalized (Jonsen, Athlin, & Suhr, 2000;Li et al, 2000;Maas et al, 2001;Rehm, 2000). Families have been restricted, however, from caring for relatives in hospitals or institutions by healthcare professionals and institutional rules (Clarke, 2000;Specht et al, 2000).…”
Section: Defining Characteristicsmentioning
confidence: 99%
“…Client factors. When a family member is diagnosed with a chronic health condition, a life-threatening circumstance, or disease relapse, families experience feelings of powerlessness, meaninglessness, and hopelessness, and they are highly dependent on healthcare professionals (Dixon, 1996;Jonsen et al, 2000;Knafl et al, 1996). Two client factors emerged: client age and client health status (e.g., chronic illness, life-threatening illness, relapse).…”
Section: Related Factorsmentioning
confidence: 99%
See 1 more Smart Citation